PSYCHOLOGICAL CHARACTERISTICS OF ADOLESCENTS IN TEACHING A FOREIGN LANGUAGE - Sultamuratova Xamre Nukusbay kizi (Journals Park Publishing, 2023)
The article describes the significance of the identified data on the psychological characteristics of adolescents for teaching a foreign language at school. On the basis of an empirical study, characteristics that do not have a correlation, as well as correlations that have a significant impact on a foreign language mark in secondary school, were identified. The data obtained contribute to the most successful construction of the educational process at school.
Keywords: psychological characteristics, teenagers, foreign language, correlation, marking criteria, objectives, linguistic ability.